Preferred orientation of phyllosilicates in Yamato-74642 and -74662, in relation to deformation of C2 chondrites - Fujimura, Akio; Kato, Manabu; Kumazawa, Mineo (1982)
P(論文) The preferred orientation of phyllosilicates in two Yamato chondrites (C2) has been examined by means of X-ray pole figure goniometry. Both C2 chondrites show almost the same textural features under the optical microscope as those of Murchison (C2) studied previously. In Yamato-74642,however, X-ray diffraction intensity of phyllosilicates is extremely weak and no information on the oriented texture could be obtained. Hydrous minerals in Yamato-74642 have probably been altered by some thermal event. Yamato-74662 possesses a weak but clear preferred orientation of phyllosilicates, indicating evidence of anisotropic deformation. The magnitude of plastic deformation is estimated to be in the order of 10%. departmental bulletin paper